PENGARUH PELATIHAN KERJA, PERAN INSTRUKTUR DAN FASILITAS PELATIHAN TERHADAP MINAT MEMBUKA USAHA KECIL ( SMALL BUSSINES ) ( STUDI KASUS PADA PESERTA DI UPT PELATIHAN KERJA TULUNGAGUNG ) - Rintis Suwasti (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study departs from the Global Jobs Pact (GJP) and remembered the paradigm shift occurs in the orientation of vocational training developed from supply-driven into a demand-driven approach that is applied in the form of entrepreneurship education. In the application of entrepreneurial education at the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training, instructor's role and use of training facilities is a driving factor in the increased interest of participants to start a small business. The purpose of this study is to determine the effect of the job training, role of the instructor and the use of training facilities and simultaneous partial to the interests of small business start-up to participants in the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training Tulungagung.This study is a quantitative correlation. The population of this study were 54 participants. While the number of samples taken all of the population that as many as 54 participants. The sampling technique implemented by total sampling technique. Methods of data collection using a questionnaire. This method is used to obtain data on the job training (X1), role of the instructor (X2), training facilities (X3) and interest in starting a small business (Y). The instruments used in the form of questions with answers that are already available consisting of 5 (five) options. To determine the existence of the effect using the t test and F test.The results of data analysis in this study indicate : (1) There is a effect of the job training (X1) against the interest of starting a small business (Y) on the participants in the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training Tulungagung. (2) There is a effect of the role of the instructor (X2) on interest starting a small business (Y) on the participants in the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training Tulungagung. (3) There is a effect of the training facilities (X3) on interest starting a small business (Y) on the participants in the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training Tulungagung. (4) There is a effect of the job training (X1), the role instructor (X2) and training facilities (X3) on interest starting a small business (Y) on the participants in the Technical Implementation Unit (Unit Pelaksana Teknis) Job Training Tulungagung.The results of this study can be used as reference material in order to develop policies to improve the performance and fix training facility, in this case some important facilities that should be addressed are the health facility, the facility (support facility) for the disabled group training, and job training car.